Understanding the ontological dynamics of digital heritage objects - Coetzee, Anton Stephen (University of the Witwatersrand, Johannesburg, 2024)
Processes of digitisation, particularly within heritage-related fields, are frequently rendered as being infinitely thin and consequently mechanically objective. The lack of engagement with their complexity results in what Latour calls “black boxing” of the processes, technology, and practices. In this work I examine techniques and practices of 3D photogrammetric recording of archaeological, ethnographic and art objects and collections. Using two exemplars in the form of a late 19th century “curio” in the KwaZulu-Natal Museum collection, and a San rock art site near Van Reenen, I unpack and attempt to understand what is contained within these black boxes. I offer digitisation as a thoughtful, object-centric practice rather than data-driven process, drawing on ideas from Caraher’s “slow archaeology” and Stobiecka’s “prosthetic archae- ology”. Objects are decontextualised and unanchored in the process of excavation or procurement, and on accession into collections they are inducted into organisational and taxonomic schemas designed to afford them value as epistemological objects. These schemata are both biased and flawed, being natural heirs of colonial knowledge systems, and are thus lacking in awareness of multiple ontological viewpoints. By reframing the original thing and the resultant digital object in an ontological sense, I attempt to characterise these systems and their constructions of authenticity. I look to past practices of three-dimensional recording and copying, namely plaster casting of specimens and sculpture, and their role in not just practices of duplication, but also in furthering the colonial project and its epistemological flows. Collection, casting and digitisation — as acts of physical and material translation — perpetrate violences involving iii removal of things from their context, remaining adrift until re-anchored within schemata and rules. Understanding and challenging the nature of these rules is critical in avoiding the risk of reinscribing procrustean colonial approaches to recording and documentation. Furthermore, as metadata and data become inextricably entangled, it becomes more diffi- cult to recreate compelling narrative and “human-readable” context from these structures. However, these shortcomings might rather offer potential, building on Lev Manovich’s ideas of database trajectories and Ruth Tringham’s “recombinant histories”, allowing new and unforeseen paths through the data. I suggest that by eschewing neoliberal metric-driven approaches to “mass digitisation” in favour of small-scale, thoughtful practices, we foreground the opportunity to learn from and with the thing during digitisation. Opening up the “black boxes” and exposing and recording craft practices helps reconnect the digital object with the original thing, and offers a reconfigured view on digital authenticity. By formally recording these acts and decisions we can also contribute to the communities of practice which have grown around many of the arcane skills of digitisation.
A research report Submitted in fulfillment of the requirements for a Master of Arts Degree f Doctor of Philosophy (History of Art), In the Faculty of Humanities , Wits School of Arts, University of the Witwatersrand, Johannesburg, 2024
Keywords: Archaeology; Heritage; Museums; 3D; digitisation; metadata; authenticity; CIDOC-CRM; photogrammetry; casts; collecting; ontologies; UCTD; SDG-9: Industry, innovation and infrastructure